Alkyl chain assisted thin film growth of 2, 7-dioctyloxy-benzothienobenzothiophene. Issue 27 (1st July 2019) - Spreitzer, Harald; Kaufmann, Benjamin; Ruzié, Christian; Röthel, Christian; Arnold, Thomas; Geerts, Yves H.; Teichert, Christian; Resel, Roland; Jones, Andrew O. F.
Abstract : An understanding of the thin film growth modes of substrate-induced polymorphs allows a deeper insight into the origin of this class of materials. Abstract : An understanding of the thin film growth modes of substrate-induced polymorphs allows a deeper insight into the origin of this class of materials. Their onset of crystallisation, the subsequent crystal growth, the evolution of the thin film morphology and the transfer to the equilibrium bulk structure are still not fully understood. This work investigates the thin film formation of a conjugated molecule with terminal alkyl chains. Thin films of 2, 7-dioctyloxy[1]benzothieno[3, 2- b ]benzothiophene were grown by physical vapor deposition on silicon oxide surfaces with varying the film thicknesses from the sub-monolayer regime up to 33 layer thick films. Additionally, the substrate temperature and deposition rate were varied. The films were investigated by atomic force microscopy, X-ray reflectivity and grazing incidence X-ray diffraction. The first growth stage is a closed monolayer with a thickness of 3 nm formed by upright-standing molecules. It is found that the substrate-induced crystal structure is already formed within the first monolayer and continues its growth up to the largest investigated film thickness. The characteristic morphology is terraced islands over the whole thickness range. On top of the first monolayer a morphology with several terrace levels appears, which is associated with a rapid increase of the surface roughness. At larger film thicknesses (≥13 nm) the number of terrace steps does not increase significantly, so that the surface roughness only increases slowly. This work shows that molecules with terminal alkyl chains can form a substrate-induced phase up to large film thicknesses without the appearance of the equilibrium bulk phase.